Narrow-band imaging cystoscopy to evaluate bladder tumours – individual surgeon variability - Herr, Harry (2009)
OBJECTIVE: To assess individual urologist variability using narrow-band imaging (NBI) cystoscopy to evaluate bladder tumours. PATIENTS AND METHODS: In all, 50 patients underwent white-light and NBI cystoscopy to evaluate for recurrent bladder tumours. Endoscopic images in each patient were independently viewed by four urologists assessing presence or absence of tumour. Their findings were correlated with biopsy results. RESULTS: In all, 26 patients had recurrent tumour and 24 had benign histology. There were no significant differences among urologists detecting recurrent tumour or in determining final pathology. CONCLUSIONS: There does not appear to be a learning curve' for adapting to NBI-surveillance cystoscopy in patients with bladder cancer.